Kestävyysarvojen yhteisluonti digitaalisten palvelujen avulla vähittäiskaupassa - Mikkilä, Annastina (2025)
As retail stores and their digital services play a central role in everyday consumer choices, it is essential to explore their potential to encourage more sustainable consumer behavior. Digital services can be used to influence consumer behaviour and address the phenomenon identified as the "green gap", in which consumer behaviour does not match the increasing positive attitude towards sustainability. A successful digital service is based on the co-creation of value, where the user defines value by using the service. Both value co-creation and customer experience are influenced by the user's background and environment, which refers to their personal contextual factors. Value co-creation in the context of digital services that promote sustainable consumption — that is, green information systems — has received little scholarly attention, and contextual factors offer a novel perspective for further research. Bringing a contextual perspective into the research on this topic will deepen the understanding of the processes of sustainable consumption and value co-creation, providing important insights for the development of digital services to enable value co-creation and sustainable consumption. The purpose of this master’s thesis is to address the identified gap in the research on sustainable value co-creation by creating an understanding of the importance of contextual factors in the use of digital services in the retail sector. 217 retail customers interested in sustainability and technology were interviewed using a qualitative laddering interview method. From the 398 ladder chains selected for the study, the attribute, consequence and value codes were first identified and then the data was analysed in terms of contextual factors. From the contextual factors present in the data, five themes were created: individual emotional and cognitive, physical and economic, sustainable normative and other normative contextual factors, and a theme of social, market and environmental factors that encompasses external contextual factors. The findings reveal how these multidimensional contextual factors influence service choice, use and the resulting co-creation of value. Among the features of digital services, those with financial incentives in particular were perceived as contributing to sustainable and other personal values. This study deepens the understanding of value co-creation enabled by digital services that support sustainability in retail, offering insights that are valuable for service design. It also demonstrates the importance and impact of contextual factors in this process.